Implementasi Aplikasi Online Single Submission Risk Based Approach (OSS-RBA) Untuk Mempermudah UMKM dalam Penerbitan Izin Usaha di Kota Mataram - Mandala, Opan; Taufik, Muhamad; Efendi, Saparudin; Wahyudi, Irfan; Kholid, Irwan (Lembaga Dongan Dosen, 2024)
Some members of Sahabat UMKM NTB face serious challenges in terms of licensing, especially because they do not yet have a valid business license in accordance with the provisions of law in Indonesia. The absence of a business license is a serious violation of Law Number 3 of 2020 concerning the Electronically Integrated Business Licensing System (SPBE), as well as other related regulations that require every business actor to have a license to carry out business activities. This condition not only causes legal problems that have the potential to result in administrative sanctions, but also has a significant impact on the sustainability of their business, such as difficulty in accessing financing and business legality. The method used in this service is through socialization and workshops aimed at members of Sahabat UMKM NTB who do not yet have a business license. This socialization activity aims to provide a deeper understanding of the importance of a business license and guide them in the process of issuing the license. As a result of this service, on October 12, the service team from Bumigora University held an OSS-RBA Application Implementation Workshop at the Mataram Mayor's Office Hall. During the workshop, several members of Sahabat UMKM NTB successfully issued their business licenses through the OSS-RBA application. In addition, the service team also provides assistance in the process of establishing a Limited Liability Company (PT) for members who need it. This activity shows a positive impact, where MSME members who do not yet have a business license can complete their permits, which in turn will strengthen the legality and sustainability of their business in the future.